Regression analysis of the influence of a chemical composition on the mechanical properties of the steel nitronic 60 - Gigović-Gekić, Almaida (Materiali in tehnologije, 2014)
Nitronic 60 (UNS S21800) is a highly alloyed austenitic stainless steel with increased amounts of manganese and silicon that has good mechanical and corrosion properties. This paper presents the results of a regression analysis of the influence of the chemical composition, i.e., the alphagenic (Si and Cr) and gamagenic (Mn and Ni) elements on the tensile properties of the steel. The results of the analysis are the equations with which we can calculate the strength for a given chemical composition when a measurement is disabled. The regression analysis showed that the strength of the steel can be increased with an increased amount of alphagenic elements and that the influence of Mn on the strength depends on the Si amount.
Keywords: austenitic stainless steel; avstenitno nerjavno jeklo; alfageni elementi; alphagenic elements; gamageni elementi; gamagenic elements; natezna trdnost; tensile properties; regresijska analiza; regression analysis